Chaperonin TRiC/CCT subunit CCT7 is involved in the replication of canine parvovirus in F81 cells - Su, Xia; Zhou, Hongzhuan; Xu, Fuzhou; Zhang, Jin; Xiao, Bing; Qi, Qi; Lin, Lulu; Yang, Bing (Frontiers in Microbiology, 2024)
Canine parvovirus (CPV) is one of the most common lethal viruses in canines. The virus disease is prevalent throughout the year, with high morbidity and mortality rate, causing serious harm to dogs and the dog industry. Previously, yeast two hybrid method was used to screen the protein Chaperonin containing TCP-1 (CCT7) that interacts with VP2. However, the mechanism of interacions between CCT7 and VP2 on CPV replication remains unclear. In this study, we first verified the interaction between CCT7 and viral VP2 proteins using yeast one-to-one experiment and co-immunoprecipitation (CoIP) experiment. Laser confocal microscopy observation showed that CCT7 and VP2 were able to co-localize and were mostly localized in the cytoplasm. In addition, the study of VP2 truncated mutant found that the interaction region of VP2 with CCT7 was located between amino acids 231 and 320. Cycloheximide (CHX) chase experiments showed that CCT7 can improve the stability of VP2 protein.After further regulation of CCT7 expression in F81 cells, it was found that the expression level of VP2 protein was significantly reduced after knocking down CCT7 expression by RNA interference (RNAi) or HSF1A inhibitor, and increased after overexpressing host CCT7. The study reveals the role of VP2 interacting protein CCT7 in the replication process of CPV, which could provide a potential target for the prevention and control of CPV.